Resveratrol Has Histone 4 and Beta-Defensin 1-Mediated Favorable Biotherapeutic Effects on Liver and Other Target Organs in Diabetic Rats - Alpaslan Tanoğlu,; Fatih Özçelik,; Fatih Hacımustafaoğlu,; Gülfidan Coşkun,; Tansel Sapmaz,; Esra Güzel Tanoğlu, (Turkish Journal of Gastroenterology, 2024)
Background/Aims: It was aimed to investigate the biochemical and histopathological effects of resveratrol and melatonin, via histone H4 and β-defensin 1, in diabetic rats.Materials and Methods: Twenty-four Sprague–Dawley male rats were categorized into 4 groups, with 6 rats in each group (control, diabetes mellitus, melatonin – diabetes mellitus, and resveratrol+diabetes mellitus). Diabetes was formed by giving streptozotocin to all groups except the control group. Melatonin, 5 mg/kg/day, was given to the melatonin – diabetes mellitus group, and resveratrol, 5 mg/kg/day, was given to the resveratrol+diabetes mellitus group via intraperitoneally for 3 weeks. Interleukin-1 beta, tumor necrosis factor alpha, histone H4, and β-defensin 1 levels were measured in the blood of all rats. The lung, liver, and kidney tissue of all rats were performed as histopathological examinations.Results: Whereas there was no difference between the other groups (P > .05), interleukin-1 beta levels of the diabetes mellitus group were found to be significantly higher compared with the control group (5.02 ± 2.15 vs. 2.38 ± 0.72 ng/mL; P < .05). Whereas histone H4 levels of the diabetes mellitus group were higher compared with the control and resveratrol+diabetes mellitus groups (7.53 ± 3.30 vs. 2.97 ± 1.57 and 3.06 ± 1.57 ng/mL; P < .05), the β-defensin 1 levels of the diabetes mellitus group were lower compared with control and resveratrol+diabetes mellitus groups (7.6 ± 2.8 vs. 21.6 ± 5.5 and 18.8 ± 7.4 ng/mL; P < .05). β-Defensin 1 levels were moderately inversely correlated with interleukin-1 beta and histone H4 levels (rs > −0.50, P < .01). Histopathological changes found in favor of target cell damage in the diabetes mellitus group were not observed in resveratrol+diabetes mellitus group.Conclusion: Resveratrol may be used as a biotherapeutic agent, which significantly reduces diabetes-induced histone H4 and interleukin-1 beta-mediated liver and other target organ damageCite this article as: Tanoğlu A, Özçelik F, Hacımustafaoğlu F, Coşkun G, Sapmaz T, Güzel Tanoğlu E. Resveratrol has histone 4 and beta-defensin 1-mediated favorable biotherapeutic effects on liver and other target organs in diabetic rats. Turk J Gastroenterol. 2024;35(3):223-231.